Gynecologic care - Keder, Lisa; Olsen, Martin E. (Cambridge medicine (Series), 2018)
Gynecologic Care provides a succinct yet comprehensive discussion of critical knowledge required for gynecologists. Concise, easily accessible chapters allow the reader to quickly review essential material for patient care, or comprehensively study the modern management of gynecology. New residents can quickly cover the breadth of gynecology, while more experienced physicians will find the materials useful for review purposes. Each chapter covers key topics listed by the Committee for Resident Education in Obstetrics and Gynecology. Gynecologic Care is part of a three book series which covers the breadth of the Obstetrics and Gynecology specialty. The other books in the series are Obstetric Care and Office Care of Women